At-Home Testing for Sexually Transmitted Infections During the COVID-19 Pandemic. Issue 1 (January 2021) - Carnevale, Caroline; Richards, Paul; Cohall, Renee; Choe, Joshua; Zitaner, Jenna; Hall, Natalie; Cohall, Alwyn; Whittier, Susan; Green, Daniel A.; Sobieszczyk, Magdalena E.; Gordon, Peter; Zucker, Jason
Abstract : Abstract: During the COVID-19 pandemic in New York City, NewYork-Presbyterian Hospital provided HIV prevention patients with gonorrhea/chlamydia testing kits at home. This report describes the program implementation to provide other sexual health clinics with a roadmap in adapting to a "new normal" in providing comprehensive sexual health care virtually to patients. Abstract : The New York-Presbyterian Hospital's HIV Prevention Program adapted to the clinical limitations of the COVID-19 pandemic by providing patients with sexually transmitted infection testing at home in an effort to maintain comprehensive sexual health services.